Drift-Alfvén wave turbulence induced particle and heat transport in I-mode pedestal plasmas - Junang Zhang; Lu Wang; Weixin Guo (Nuclear Fusion)
In this work, most of the weakly coherent mode (WCM) characteristics and the level of transport coefficients observed in I-mode pedestal plasmas of C-Mod are reproduced theoretically. The dispersion relation of drift-Alfvén wave (DAW) is analytically solved for both drift-wave (DW) and Alfvén wave branches, and the WCM is identified to be the DW branch. The frequency of DW branch in the laboratory frame is about 200 kHz, the poloidal phase velocity propagating in the direction of electron diamagnetic drift is around $7.0\,{\text{km}} · {{\text{s}}^{ - 1}}$ , and the relative magnitude of normalized fluctuations of electron temperature, density and magnetic field are $| {\frac{{{{\tilde T}_e}}}{{{T_{e0}}}}} |/| {\frac{{{{\tilde n}_e}}}{{{n_0}}}} | ≈ 0.1$ and $| {{\tilde{\mathbf b}}} |/| {\frac{{{{\tilde n}_e}}}{{{n_0}}}}| ≈ 8.3 × {10^{ - 4}}$ , respectively, which are all consistent with the characteristics of WCM observed in C-Mod experiment. Moreover, the modulation-induced transport coefficients in the presence of DAW turbulence are calculated. It is found that the electromagnetic part of transport coefficient is about 10% of the electrostatic part. The particle diffusivity is $0.21\,{{\text{m}}^2} · {{\text{s}}^{ - 1}}$ , which is about twice of the experimental value. Meanwhile, the electron thermal conductivity is $0.27\,{{\text{m}}^2} · {{\text{s}}^{ - 1}}$ , and is in very good agreement with the corresponding experimental and simulation values. These results may advance the understanding of the underlying physics of turbulence and transport in the I-mode pedestal plasmas.